A comparative analysis on how much individuals are left behind in the former state socialist countries of the European Union - Bárcena-Martín, Elena María; García-Pardo, Francisca; Pérez-Moreno, Salvador Jesús (Elsevier, 2024)
This paper examines the extent to which individuals from the former state socialist countries of the EU’s Central and Eastern European (CEE) countries have been left behind compared to the rest of EU individuals from Western European (WE) countries and across countries within the CEE bloc. To this end, a fuzzy approach is applied to a multidimensional setting made up of income, material deprivation, and work intensity to measure the ‘Leaving no one behind’ (LNOB) principle of the 2030 Sustainable Development Agenda. A certain process of convergence is found between both blocs of countries over the period 2007–2019 due to a decrease in the level individuals were left behind in the CEE countries, as well as an increase in the level individuals were left behind in the WE countries in the years following the 2007–2008 financial crisis. Significant cross-country disparities in the degree individuals lag behind are also revealed among the CEE countries related to the different models of post-socialist capitalism established in these countries and their subsequent development after joining the EU.
Keywords: Paises socialistas; Unión europea--Aspectos económicos; Unión europea--Europa Oriental; Unión europea--Integración económica; Former state socialist countries; Fuzzy approach; Leaving no one behind; Work intensity; Income Material deprivation